ANALYSIS OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN FORMING THE CHARACTER OF STUDENTS - Muafiq, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to determine the characteristics of students at MTS Riyadlus Sholihin and the role of Islamic Religious Education Teachers in efforts to shape the character of MTS Riyadlus Sholihin students. The character formation of students in question is the method used by the school, both teachers and other parties, effectively and efficiently, in forming the character of students at MTS Riyadlus Sholihin. The research method used involved an initial survey to assess teachers' level of awareness and needs regarding learner characteristics, followed by appropriate program design and implementation. Data obtained through surveys, observations and interviews are used to evaluate the impact of the program on student characteristics. as a result, on learning productivity in the classroom. The results of the research show a significant increase in character and spiritual intelligence education efforts in this school taking a strong foundation from religious and ethical values, which are taught by Islamic Religious Education and Moral Education teachers. Through various roles such as educators, teachers, mentors, trainers, advisors, and role models, Islamic Religious Education teachers play a central role in helping students understand, internalize, and apply moral values in real life.